PENGOLAHAN LIMBAH BAMBU MENJADI TRIMMINGS DAN AKSESORIS FESYEN - Arsallya, Chita Fefri (ATRAT: Jurnal Seni Rupa, 2017)
Natural fiber has its own characteristics that might be able to create some innovative works. To optimize the use of various natural fibers, the writer treated bamboo waste to increase its value so that it becomes more interesting and varied. This is due to abundance of abandoned bamboo waste and lack of its utilization. This bamboo waste processing study was conducted through several experiments using some techniques that involve scouring and bleaching with chemicals ingredients and also some processing techniques. Products that will be produced in this exploration of bamboo waste processing are trimmings and fashion accessories. The results of this study are expected to reduce the disposal of natural waste such as bamboo waste. The products made from bamboo waste can be fashion items that increase their economic, aesthetics and functional values.Keywords: Bamboo Waste, Fashion Accessories, Trimmings___________________________________________________________________ Serat alam memiliki karakteristik tersendiri yang memungkinkan terciptanya karya-karya yang inovatif. Untuk mengoptimalkan penggunaan serat alam yang variatif, penulis mengolah limbah bambu untuk meningkatkan nilai tambah dari limbah tersebut sehingga menjadi lebih menarik dan variatif. Hal ini dikarenakan oleh banyaknya limbah bambu yang dibuang begitu saja dan kurangnya pemanfaatan limbah bambu yang secara optimal. Penelitian pengolahan limbah bambu dilakukan dengan beberapa eksperimen menggunakan teknik scouring dan bleaching yang melibatkan zat kimia serta beberapa teknik pengolahan. Produk yang akan dihasilkan dalam eksplorasi pengolahan limbah bambu ini berupa trimmings dan aksesoris fesyen. Diharapkan hasil penelitian pengolahan limbah bambu ini dapat mengurangi pembuangan sumber daya alam berupa limbah bambu. Produk yang dihasilkan dapat menjadi produk fesyen yang optimal serta meningkatkan nilai ekonomi, estetika, dan fungsional dari limbah tersebut. Kata Kunci: Aksesoris Fesyen, Limbah Bambu, Trimmings